2021
DOI: 10.1016/j.heliyon.2021.e07512
|View full text |Cite
|
Sign up to set email alerts
|

Halotolerant and metalotolerant bacteria strains with heavy metals biorestoration possibilities isolated from Uburu Salt Lake, Southeastern, Nigeria

Abstract: Environmental contaminations by heavy metals are currently an increasing public health concern globally. One key challenge of these toxic metals is the extremely difficulties involved in their detoxification from the environment and effluents because of their non-degradability. An efficient biologic agent with potentials of remediating these toxic metals may ease these ever-increasing problems. We reported toxic metals tolerance and bioremediation potentials of novel bacteria sp. Strains USL2S, USL4W and USL5W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…While the highest NaCl concentration tested in this study only reached 1.05% (4X artificial sweat) and is not considered a high salt concentration, many skin microorganisms are highly halotolerant and capable of withstanding drastic changes in osmotic pressure, including Staphylococcus and Corynebacterium species (47)(48)(49)(50)(51)(52)(53). In addition, nearly all other genera in this study have reports of species being identified as halotolerant (54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 81%
“…While the highest NaCl concentration tested in this study only reached 1.05% (4X artificial sweat) and is not considered a high salt concentration, many skin microorganisms are highly halotolerant and capable of withstanding drastic changes in osmotic pressure, including Staphylococcus and Corynebacterium species (47)(48)(49)(50)(51)(52)(53). In addition, nearly all other genera in this study have reports of species being identified as halotolerant (54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 81%
“… Holan and Volesky (1994) stated that sorption of the metals increases with increasing valence and the atomic number of metals, which was partially agreed upon by the current study. Orji et al (2021) investigated the biosorption efficiency of Klebsiella sp. USL25 for removing Hg 2+ , Pb 2+ , Cd 2+ , and Ni 2+ and obtained the following results: 85, 97.13, 73.33, and 86.06%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, former mining sites are associated with non-alkaline or even acidic pH, which promotes metal leaching [12]. At circumneutral pH such as the niche investigated, co-occurrence of (sulfate) salt ions and metal ions imposes extra stress on the microorganisms, which results in co-tolerance [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…However, former mining sites are associated with circum-neutral or even acidic pH, the latter promoting metal leaching. The co-occurrence of metal ions poses another stress on the microbial community, which results in co-tolerance [10,11].…”
Section: Introductionmentioning
confidence: 99%